Medium to large-sized mammals of the augusto ruschi biological reserve, São Paulo state, Brazil - Fornitano, Larissa [UNESP]; Angeli, Thaís [UNESP]; Costa, Rômulo Theodoro [UNESP]; Olifiers, Natalie; Bianchi, Rita de Cassia [UNESP] (Oecologia Australis, 2015)
Although São Paulo state presents two biodiversity hotspots – the Cerrado and the Atlantic Forest – it currently retains only 13% of its native vegetation, which is divided into 8,300 fragments harboring as a whole at least 220 mammal species. This study aims to survey mammalian species of medium to large size in a protected area of São Paulo, the Augusto Ruschi Biological Reserve, which is composed of five forest fragments. We used 562 camera-trap-nights, footprint surveys, and opportunistic visualizations to record species. Species richness was estimated by the presence/absence of animals at the camera-trap station and using the first-order Jackknife estimator. The estimated species richness was 10.99 (± 1.4 standard deviation), but species richness reached 16 species when other types of records were considered. The species richness of medium and large-sized mammals in the area is considerably high, with four species that are vulnerable to extinction. However, the recorded species are not fully protected due to the presence of anthropogenic activities. Based on our results, we recommend specific management actions to enhance species conservation in the reserve.
Keywords: Camera-trap; Fragment; Species richness